Common factors in psychotherapy - (:unkn) unknown (Springer International Publishing, 2018)
Many meta-analyses and research study reviews affirm the comparable effectiveness of psychotherapies in adult patients. This points to common (or core) factors in diverse schools of psychotherapy. In this chapter, we review the core factors that we believe are fundamentally responsible for transformative change in psychotherapy processes. These core factors include the therapeutic alliance, empathy, goal consensus and collaboration, positive regard and affirmation, mastery, congruence/genuineness, mentalization and emotional experience. Evidence-based research on common factors has shown that relationship factors in a therapeutic dyad or group setting predict the outcome of psychotherapy, which is related to some of these common factors, and is also found to correlate with improved levels of functioning (Fisher et al. Psychotherapy 53:105-116, 2016). The effectiveness of psychotherapies may rely more on commonalities rather than on differences of theory and technique. © Springer International Publishing AG, part of Springer Nature 2019. All rights reserved.